Murine pluripotent stem cells derived scaffold-free cartilage grafts from a micro-cavitary hydrogel platform - Fu, Jiayin (2016)
By means of appropriate cell type and scaffold, tissue-engineering approaches aim to construct grafts for cartilage repair. Pluripotent stem cells especially induced pluripotent stem cells (iPSCs) are of promising cell candidates due to the pluripotent plasticity and abundant cell source. We explored three dimensional (3D) culture and chondrogenesis of murine iPSCs (miPSCs) on an alginate-based micro-cavity hydrogel (MCG) platform in pursuit of fabricating synthetic-scaffold-free cartilage grafts. Murine embryonic stem cells (mESCs) were employed in parallel as the control. Chondrogenesis was fulfilled using a consecutive protocol via mesoderm differentiation followed by chondrogenic differentiation; subsequently, miPSC and mESC-seeded constructs were further respectively cultured in chondrocyte culture (CC) medium. Alginate phase in the constructs was then removed to generate a graft only comprised of induced chondrocytic cells and cartilaginous extracellular matrix (ECMs). We found that from the mESC-seeded constructs, formation of intact grafts could be achieved in greater sizes with relatively fewer chondrocytic cells and abundant ECMs; from miPSC-seeded constructs, relatively smaller sized cartilaginous grafts could be formed by cells with chondrocytic phenotype wrapped by abundant and better assembled collagen type II. This study demonstrated successful creation of pluripotent stem cells-derived cartilage/chondroid graft from a 3D MCG interim platform. By the support of materials and methodologies established from this study, particularly given the autologous availability of iPSCs, engineered autologous cartilage engraftment may be potentially fulfilled without relying on the limited and invasive autologous chondrocytes acquisition.